Influence of ammonia-contaminated fly ash from selective catalytic reduction process on the properties of Portland-fly ash blended cement and geopolymer composites - Teewara Suwan; Mizi Fan; Hong S. Wong; Peerapong Jitsangiam; Chayanon Hansapinyo; Prinya Chindaprasirt (Case Studies in Construction Materials)
Fly ash, a by-product of coal-fired power plants, finds valuable application in the cement and concrete industry due to its pozzolanic properties. Environmental concerns necessitate the use of Selective Catalytic Reduction (SCR) systems to reduce nitrogen oxide emissions; however, this process introduces residual ammonia onto the fly ash, known as SCR-fly ash, which may affect its properties. This study investigates the characteristics and suitability of SCR-fly ash as a supplementary cementitious material in Portland cement and geopolymer cement composites, compared to conventional high-calcium fly ash. The results show that Portland-fly ash blended cement mixtures containing 20 % SCR-fly ash achieve comparable engineering properties to those with high-calcium fly ash, with a slight reduction in compressive strength of ∼ 3.4 % at 28 days. Geopolymers with SCR-fly ash exhibit a significantly lower (∼ 52.8 %) compressive strength than that of high-calcium fly ash 28 days. However, SCR-fly ash requires a resting period of at least 20 days to reduce ammonia content before use. The larger particle size and presence of residual ammonia can react to form detrimental gypsum or ammonium salts that lead to reduced strength. Therefore, SCR-fly ash may need to be chemically treated to be suitable as a geopolymer precursor. Overall, this work provides crucial insights into the potential utilization of SCR-fly ash in the cement and concrete industry, promoting resource recovery and environmental sustainability.